(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the influence of role-play activities on improving speaking fluency among secondary school students. It examines how role-play strengthens communicative competence, encourages spontaneous speech, reduces anxiety, and enhances learners’ confidence in real-life communication. The paper also highlights the psychological, linguistic, and pedagogical factors that make role-play an effective tool in modern language classrooms. Findings suggest that role-play not only improves fluency, but also promotes active participation, interaction, and meaningful language use.